2016
DOI: 10.1016/j.nicl.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Combining anatomical, diffusion, and resting state functional magnetic resonance imaging for individual classification of mild and moderate Alzheimer's disease

Abstract: Magnetic resonance imaging (MRI) is sensitive to structural and functional changes in the brain caused by Alzheimer's disease (AD), and can therefore be used to help in diagnosing the disease. Improving classification of AD patients based on MRI scans might help to identify AD earlier in the disease's progress, which may be key in developing treatments for AD. In this study we used an elastic net classifier based on several measures derived from the MRI scans of mild to moderate AD patients (N = 77) from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 43 publications
8
104
1
Order By: Relevance
“…Furthermore, in line with previous work, we observed that concatenating all measures did not result in the most accurate classification model and as more measures were added the level of improvement became less apparent [29,31,61]. The marginal improvements observed for some measures or combinations may indicate a negligible contribution to the model.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, in line with previous work, we observed that concatenating all measures did not result in the most accurate classification model and as more measures were added the level of improvement became less apparent [29,31,61]. The marginal improvements observed for some measures or combinations may indicate a negligible contribution to the model.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the role of rsfMRI as a separate measure for disease-type classifications has not yet been established. It has found limited application for single subject disease-type classifications [27,29,30,32]. In AD versus control classifications its performance rates are consistently among the lowest compared with other MRI measures [29,30,32] and we also found that rs-fMRI as a single measure was neither effective in differentiating dementia types nor between patients and controls subjects.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations